Development of Digital Learning Media for Community-Based Education: A Collaborative Innovation and Literacy Framework - Daddy Darmawan; Puji Hadiyanti; Setiawan Wibowo; Rahmat Syah; Muhammad Fadhlan Abdillah (Journal of Nonformal Education, 2025)
Background: The rapid advancement of digital technology has transformed global education, yet disparities in access persist, particularly in low-income and rural regions. Digital literacy—encompassing technical, critical, and ethical competencies—remains underdeveloped due to insufficient teacher training and infrastructural limitations. Research Objectives: This study aims to (1) assess the effectiveness of FOCIL in improving digital literacy, (2) evaluate its socio-cultural and infrastructural adaptability, and (3) identify key features that enhance learning outcomes in underserved communities. Research Method: A mixed-methods sequential exploratory design was employed, combining qualitative stakeholder interviews, observational studies, and document analysis, followed by quantitative usability and field trials. Research Findings: The FOCIL platform significantly enhanced literacy outcomes, with participants demonstrating greater progress than those using conventional methods. Learning modules that incorporated local wisdom, such as regional folktales, proved more engaging and achieved higher completion rates than generic materials. The platform’s low-bandwidth design effectively supported learners in rural areas, enabling continued access through offline mode. Interactive features, particularly discussion forums and gamification, played a central role in boosting engagement and reinforcing learning gains. Conclusion: FOCIL effectively bridges digital divides by aligning with socio-cultural contexts, overcoming infrastructural barriers, and employing evidence-based pedagogies. Challenges include server latency and the need for teacher training. Future iterations should integrate AI-driven feedback and expand partnerships for scalability. Novelty/Originality/Value:  This study contributes a validated Cultural-Technological Implementation Framework and an open-source, adaptive platform tailored for resource-constrained settings. It advances the discourse on equitable digital education by demonstrating how community-centric design and hybrid learning models can enhance literacy and inclusion.